Dopamine D1 or D2 receptor‐expressing neurons in the central nervous system. (24th April 2017) - Wei, Xiaoyan; Ma, Tengfei; Cheng, Yifeng; Huang, Cathy C.Y.; Wang, Xuehua; Lu, Jiayi; Wang, Jun
Abstract: Dopamine signals mainly through D1 receptors (D1Rs) and D2 receptors (D2Rs); D1R‐expressing or D2R‐expressing neurons contribute to distinct reward and addictive behaviors. Traditionally, transgenic mice expressing green fluorescent protein (GFP) under D1R or D2R promoters are used for fluorescent verification in electrophysiology studies, whereas Cre mice are employed for behavioral research. However, it is unknown whether the same neuronal populations are targeted in GFP and Cre mice. Additionally, while D1Rs and D2Rs are known to be expressed in different striatal neurons, their expression patterns outside the striatum remain unclear. The present study addressed these two questions by using several transgenic mouse lines expressing fluorescent proteins (GFP or tdTomato) or Cre under the control of D1R or D2R promoters. We found a high degree of overlap between GFP‐positive and Cre‐positive neurons in the striatum and hippocampus. Additionally, we discovered that D1Rs and D2Rs were highly segregated in the orbitofrontal cortex, prefrontal cortex, dorsal and ventral hippocampus, and amygdala: ~4–34 percent of neurons co‐expressed these receptors. Importantly, slice electrophysiological studies demonstrated that D1R‐positive and D1R‐negative hippocampal neurons were functionally distinct in a mouse line generated by crossing Drd1a ‐Cre mice with a Cre reporter Ai14 line. Lastly, we discovered that chronic alcohol intake differentially altered D1R‐positive and D2R‐positive neuron excitability in the ventral CA1. These data suggest that GFP and Cre mice target the same populations of striatal neurons, D1R‐expressing or D2R‐expressing neurons are highly segregated outside the striatum, and these neurons in the ventral hippocampal may exert distinct roles in alcohol addiction. Abstract : D1(D2)‐GFP and D1(D2)‐Cre mice target the same populations of striatal neurons. D1R‐expressing and D2R‐expressing neurons are highly segregated in the cortex, hippocampus, and amygdala. Excessive alcohol consumption distinctly regulates excitability of D1R‐expressing and D2R‐expressing ventral CA1 neurons.